2014
DOI: 10.1186/s12866-014-0236-0
|View full text |Cite
|
Sign up to set email alerts
|

Cell death and ultrastructural alterations in Leishmania amazonensis caused by new compound 4-Nitrobenzaldehyde thiosemicarbazone derived from S-limonene

Abstract: BackgroundThe treatment of leishmaniasis with pentavalent antimonials is problematic because of their toxicity. Investigations of potentially active molecules are important to discover less toxic drugs that are viable economic alternatives for the treatment of leishmaniasis. Thiosemicarbazones are a group of molecules that are known for their wide versatility and biological activity. In the present study, we examined the antileishmania activity, mechanism of action, and biochemical alterations produced by a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 36 publications
(27 reference statements)
4
44
0
5
Order By: Relevance
“…The increased deposition of lipid bodies may suggest the interference of drug with the phospholipids and sterol content. Similar effect on lipid deposition in parasites of Leishmania and Trypanosome was earlier reported with various drugs like 22,26-azasterol, S-limonene, and amiodarone (Britta et al 2014;de Macedo-Silva et al 2011;Rodrigues et al 2002).…”
Section: Discussionsupporting
confidence: 64%
“…The increased deposition of lipid bodies may suggest the interference of drug with the phospholipids and sterol content. Similar effect on lipid deposition in parasites of Leishmania and Trypanosome was earlier reported with various drugs like 22,26-azasterol, S-limonene, and amiodarone (Britta et al 2014;de Macedo-Silva et al 2011;Rodrigues et al 2002).…”
Section: Discussionsupporting
confidence: 64%
“…On the other hand, the normal SGN is tough, so it is insusceptible to the damage caused by electromagnetic radiation. However, in the lipopolysaccharide-induced inflammation in vitro model, we found that cellular ultrastructure changes, such as mitochondrial vacuoles, karyopyknosis, and presence of lysosomes and autophagosome, are considered to be an indicator of cell damage [ 31 ]. We consider that the SGN maybe in a fragile state after pretreatment with low-concentration pretreatment of LPS (40 μg/ml), and the sensitivity of SGN to damage caused by 4 W/kg radiation is increased in this condition.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that beta-caryophyllene, alpha-pinene, and limonene are compounds with antileishmanial activities (19)(20)(21). In this regard, one previous study showed that F. vulgaris is rich in these compounds (10).…”
Section: Discussionmentioning
confidence: 98%